Research of tools for monitoring changes in natural and anthropogenic-transformed ecosystems. Issue 2 (December 2021) - Belyaev, A; Kramarov, S; Mityasova, O; Popov, O; Khramov, V
Abstract: Decarbonization issues are one of the main strategic directions of modern environmental development today. New technologies of agricultural use of soils are used to fix carbon in the soil in the form of humus, which ultimately helps to reduce the greenhouse effect and actively affects the amount of carbon entering the atmosphere. The use of open data of remote sensing of the Earth from space (further - RSE) together with the data of satellite monitoring of the Normalized Difference Vegetation Index (NDVI) can allow us to obtain new methods of carbonation analysis. In this paper, we consider the possibilities of such use of standard NDVI data together with a more accurate definition of specific boundaries of agricultural fields in order to increase the accuracy of research results. This article shows the results of processing data and images obtained using open crop monitoring data. The proposed technology is proposed by us as an additional tool for monitoring changes in the ecosystems of the regions.